Implementation of decisions by the African Court and African Commission on human and peoples' rights on indigenous peoples in Kenya - Viljoen, Frans (University of Pretoria, 2024)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.